Analysis of Urban Agglomeration in Economic and Legal Perspectives (A Study on the Development of Industrial Agglomeration Areas in Semarang City) - Andi Tri Haryono; Muhamad Hasan Muaziz; Abdul Kadir Jaelani (Faculty of Law, Universitas Pekalongan, 2021)
This study tries to analyze the implementation of laws and policies regarding the development of urban agglomerations, analyze agrarian law regulations in Indonesia addressing industrial estate issues, and analyze the leading sectors and economic potential of the city of Semarang. In this study, the authors use the Base Sector Analysis/LQ Analysis, Economic Sector Performance Analysis/Shift Share Analysis, Growth Ratio Model Analysis/GRM, Klassen Typology Analysis, Overlay Techniques, and SWOT Analysis to measure the competitive advantage of each element), and provide policy recommendations for the government as well as for industry players. The object of this research is spread over several industrial areas located in Semarang City including Wijaya Kusuma Industrial Area, Candi Industrial Area, BSB Industrial Park, and Terboyo Industrial Estate. The findings of this study are that it is known that leading sectors such as warehousing, financial services, transportation, retail, real estate, trade, and construction are economic bases that are growing rapidly and can support the development of urban agglomerations.